PENGARUH PENGALAMAN KERJA, KEPUASAN KERJA, DAN STRES KERJATERHADAP KINERJA KARYAWAN DI PT. BPR GUNUNG KAWI SEMARANG - Imanuel Yudi A.P, 11.05.51.0066 (Students Journal of Economic and Management, 2015)
This study was to examine and analyze on the effect of work experience, job satisfaction and work stress on employee performance. The object of this study were all employees of PT. RB Gunung Kawi Semarang. The sampling technique in this research is to use the census method, using the whole population is numbered 52 employees using the techniques of data collection questionnaire (questionnaire) by distributing a list of statements to the respondent for information. Data were analyzed using factor analysis to test the validity of the statement items, Cronbach alpha formula to test the reliability of each - each independent variable was tested using regression analysis. Results of this study are: (1) Work experience positive and significant effect on employee performance. (2) Job satisfaction and significant positive effect on employee performance. (3) Work stress is a significant negative effect on employee performance. Keywords: Work Experience, Job Satisfaction, and Job Stress